1988
DOI: 10.1111/j.1399-3054.1988.tb06623.x
|View full text |Cite
|
Sign up to set email alerts
|

Germination of seeds of annual and biennial celery (Apium graveolens)

Abstract: Seeds of 4 annual cultivars of celery (Apium graveolens L. No. 15, 16, 17 and 143) were able to germinate in the dark, under high temperature, in relatively high concentrations of NaCl solutions and in the presence of relatively high concentrations of the inhibitors of the biosynthesis of gibberellin, paclobutrazol and ancymidol. Seeds of two biennial cultivars [Florida and Earlibell (EB)] showed very low germinability, or failed to germinate under the same conditions. These results are discussed in terms of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…A. graveolens is native to eastern Mediterranean, however, the wide distribution of wild ecotypes of the species makes definition of its origin uncertain [39]. It is usually a biannual plant, which is cultivated as an annual crop, however, annual cultivars also exist which are best suited for dry fruit and seed production [40].…”
Section: Cultivationmentioning
confidence: 99%
“…A. graveolens is native to eastern Mediterranean, however, the wide distribution of wild ecotypes of the species makes definition of its origin uncertain [39]. It is usually a biannual plant, which is cultivated as an annual crop, however, annual cultivars also exist which are best suited for dry fruit and seed production [40].…”
Section: Cultivationmentioning
confidence: 99%
“…However, it was concluded that it does not inhibit GA production or lower its content in higher plants [16] . Assuming that for the germination of celery seeds de novo synthesis or metabolism of endogenous GA's is a prerequisite [15], then on the basis of the results presented in Figure 2 it is plausible to conclude that daminozide and chloremquat chloride do interfere with these processes . Cytokinins (BA or kinetin and also zeatin and zeatin riboside-data not shown) acted synergistically with GA4/7 to overcome the inhibition of the whole seeds only (caused by the growth retardants) and only in the dark ( Figure 1 and Table 1 from plants pretreated with paclobutrazol [4] .…”
Section: Discussionmentioning
confidence: 99%
“…143 are able to germinate in the dark and in the presence of paclobutrazol . These conditions prevent the germination of biennial celery seeds [15] . However, the germination of seeds of the annual cv .…”
Section: Introductionmentioning
confidence: 99%
“…1975; Jacobsen et al . 1976; Pressman et al . 1977, 1988; Biddington & Thomas 1979; Jacobsen & Pressman 1979; Coolbear et al .…”
Section: Introductionmentioning
confidence: 99%
“…Because of the economic importance of Apium graveolens L. (celery), its seeds have received considerable research attention (Thompson 1974a,b;Thomas et al 1975;Jacobsen et al 1976;Pressman et al 1977Pressman et al , 1988Biddington & Thomas 1979;Jacobsen & Pressman 1979;Coolbear et al 1991;Pérez-García et al 1995). Seeds of this species have a small, linear-shaped embryo that is surrounded by endosperm.…”
Section: Introductionmentioning
confidence: 99%